Internalisasi Nilai-Nilai Panca Jiwa Santri dalam Membentuk Karakter Humanis Santri di Pesantren - Nafilah, Zitkiyatun; Pathollah, Akhmad Ghasi (Kependidikan Islam Fakultas Agama Islam, 2023)
This research discusses the internalisation of the Five Souls values in shaping humanist character in Manbaul Ulum Islamic Boarding School. Pesantren has a strategic role in fostering the morality and character of students through the application of strict discipline and practices that are in accordance with the theory of organisational behaviour. The concept of Five Souls values becomes the main foundation in pesantren education, where values such as responsible freedom, sincerity, simplicity, and humanism are emphasised. Through the internalisation of these values, santri are expected to develop a strong humanist character and be able to face various challenges in life. This research uses a descriptive qualitative approach with data collection through direct observation in the field. The results showed that the concept of Five Souls values has a positive contribution in shaping the character of santri and making pesantren an educational institution that plays an important role in the development of morality and individual personality.